Effect of Solution and Dry Processing Techniques on the Optical and Transport Properties of Inorganic CsPbBr3 Perovskite Films. Issue 1 (1st October 2022) - Sujith, P; Pratheek, M; Aiswarya, M; Babu, Saranya; Parne, Saidi Reddy; Predeep, P.
Abstract : Cesium-based inorganic CsPbBr3 perovskite material possesses remarkable optoelectronic properties, such as high light absorption coefficient, high carrier mobility, and long diffusion length, and hence has promising applications in solar cells, photo-detectors, and high-energy radiation detectors, among others. Because of its simplicity, low cost, and high efficiency, spin-coating deposition for the CsPbBr3 perovskite layer for such diverse applications has been widely used. However, the spin-coating technique has technological constraints when it comes to uniformly deposit large-area films. Thermal evaporation, on the other hand, is inexpensive and produces a uniform and repeatable thin film. In this study, the stability, energy band alignment, surface morphologies, and light absorption of a CsPbBr3 perovskite layer produced by spin coating and thermal evaporation are investigated and discussed.